Stability, Boundedness, and Lagrange Stability of Fractional Differential Equations with Initial Time Difference - Muhammed Çiçek; Coşkun Yakar; Bülent Oğur (The Scientific World Journal)
Differential inequalities, comparison results, and sufficient conditions on initial time difference stability, boundedness, and Lagrange stability for fractional differential systems have been evaluated.